2018
DOI: 10.1002/pon.4666
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with romantic relationship formation difficulties in women with breast cancer

Abstract: Un-partnered women who place high importance on appearance for their self-worth and who report poor body image and low self-compassion are at risk of experiencing difficulties in forming new romantic relationships after breast cancer. Future interventions should target these variables to facilitate romantic dating during cancer survivorship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
1
9
0
1
Order By: Relevance
“…The fact that the extent of the surgery has proved to be insignificant in this matter suggests that the issue of body acceptance should be given particular importance not only in the case of women after mastectomy but also in women treated by BCT. In this scope, our results are similar to those of other authors who observed symptoms of distress in women with breast cancer due to the discrepancy between the expected and the actual appearance after surgery 8,32,33. Another observation concerned the intimate relationship with a partner.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The fact that the extent of the surgery has proved to be insignificant in this matter suggests that the issue of body acceptance should be given particular importance not only in the case of women after mastectomy but also in women treated by BCT. In this scope, our results are similar to those of other authors who observed symptoms of distress in women with breast cancer due to the discrepancy between the expected and the actual appearance after surgery 8,32,33. Another observation concerned the intimate relationship with a partner.…”
supporting
confidence: 91%
“…Our analysis did not reveal differences in the result between the groups of women currently in a relationship and those living alone. Also, other authors suggest that single women, after receiving treatment against breast cancer, can have potential problems with entering into romantic relationships with men, which correlate with the increased level of fear, dissatisfaction with the body, and low evaluation of their own interpersonal competence . The next result, revealing higher scoring on the K scale, obtained by women after surgical treatment, may speak for some compensation strategies undertaken following the removal or mutilation of the breast, some of them manifested by a willingness to accentuate femininity with feminine attributes, such as clothes or make‐up.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic and medical data and t ‐test comparisons of mean outcomes are depicted in Table . The current sample displays: (a) similar DASS Stress scores to other samples of similar aged breast cancer survivors recruited from Breast Cancer Network Australia and elsewhere, and higher scores than healthy individuals; (b) similar scores on self‐compassion to older adults(mean age = 51.26) and other breast cancer survivor samples; (c) higher (worse) scores on negative IOC than breast and non‐Hodgkin lymphoma survivors; (d) Overall, the present sample is generally securely attached, with a tendency to be less secure for the attachment avoidance dimension. The mean scores on attachment anxiety in the present study M = 2.51 (SD = 1.05) are slightly (but not significantly) lower than that reported in a study of healthy community adults in Serbia M = 2.85 (SD = 1.45) and similar to that reported in an illness sample of individuals with ulcerative colitis M = 2.5 (SD = 1.4).…”
Section: Resultsmentioning
confidence: 51%
“…Since the partners' insecure attachment has been linked with the cancer survivors' poor adjustment, attachment‐based couple therapy (eg, emotionally focused couple therapy) may be useful for insecurely attached couples. This is particularly pertinent as self‐compassion is not only believed to stem from prior interpersonal interactions but also implicated in romantic relationship formation post‐breast cancer and the quality of dyadic adjustment and communications among couples in the cancer context …”
Section: Discussionmentioning
confidence: 99%
“…Bu hassas popülasyonun cinselliği farklı sosyokültürel yapılar içerisindeki değişimlerden de çok yönlü olarak etkilenmektedir. [38][39][40] Aile üyeleri, kanserli hastalar için sosyal ve duygusal desteğin ana kaynağıdır ve hastalıkla baş etmede en önemli yapıdır. [4] Meme kanseri tanısı sonrası çiftlerin hastalık ve sonrasındaki süreçle nasıl baş edeceklerini, bunu etkileyen kültürel faktörleri analiz eden araştırmacılar, dört kültür faktörünü ortaya koymuşlardır.…”
Section: öZunclassified